2013
DOI: 10.2460/ajvr.74.5.665
|View full text |Cite
|
Sign up to set email alerts
|

Effects of isoflurane with and without dexmedetomidine or remifentanil on heart rate variability before and after nociceptive stimulation at different multiples of minimum alveolar concentration in dogs

Abstract: On the basis of SDNN and high-frequency power values, anesthetic levels between 0.75 and 1.5 MAC within the same anesthetic protocol could be differentiated, but with a large overlap among protocols. Usefulness of standard HRV variables for assessment of anesthetic depth and nociception in dogs is questionable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 38 publications
2
9
1
1
Order By: Relevance
“…Anesthesia was essential for this study, both to be able to undertake the surgical interventions and to reduce movement artefact during HRV assessment, but is also known to profoundly alter autonomic regulation. However, lower concentrations of isoflurane, such as in the current study, have been reported to induce a reflex increase in sympathetic tone [ 47 ], which may be considered further support to the findings in the current study that the C5aR is required for maximal responsiveness in the β1-AR. Furthermore, it should be recognized that HRV only provides a very indirect marker of autonomic regulation.…”
Section: Discussionsupporting
confidence: 88%
“…Anesthesia was essential for this study, both to be able to undertake the surgical interventions and to reduce movement artefact during HRV assessment, but is also known to profoundly alter autonomic regulation. However, lower concentrations of isoflurane, such as in the current study, have been reported to induce a reflex increase in sympathetic tone [ 47 ], which may be considered further support to the findings in the current study that the C5aR is required for maximal responsiveness in the β1-AR. Furthermore, it should be recognized that HRV only provides a very indirect marker of autonomic regulation.…”
Section: Discussionsupporting
confidence: 88%
“…This finding corresponds to the findings from studies on other species. An epidural administration of dexmedetomidine was able to reduce the isoflurane requirements up to 33% in dogs [25], and a CRI of dexmedetomidine in dogs at the same rate as in the present study had a MAC-sparing effect between 41% [26] and 59% [27]. In cats, pharmacokinetic studies have shown a dose-dependent reduction in isoflurane requirements with an estimated maximal sparing effect of approximately 80% [28].…”
Section: Discussionmentioning
confidence: 73%
“…Furthermore, anaesthesia in the present study was induced with propofol and maintained with sevoflurane. Different results may be obtained using other drugs, especially those affecting HR variability such as atropine, opioids or a 2 -adrenoceptor agonists (Voigt et al 2013).…”
Section: Discussionmentioning
confidence: 99%